2004
DOI: 10.1186/1477-5751-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunological parameters in girls with Turner syndrome

Abstract: Disturbances in the immune system has been described in Turner syndrome, with an association to low levels of IgG and IgM and decreased levels of T-and B-lymphocytes. Also different autoimmune diseases have been connected to Turner syndrome (45, X), thyroiditis being the most common.Besides the typical features of Turner syndrome (short stature, failure to enter puberty spontaneously and infertility due to ovarian insufficiency) ear problems are common (recurrent otitis media and progressive sensorineural hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
15
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 15 publications
(20 reference statements)
7
15
0
4
Order By: Relevance
“…Interestingly, two studies have reported a decrease in the CD4 to CD8 lymphocyte ratio in the peripheral blood of TS patients [12,14]. Consistent with these two previous reports, we also found that TS patients have a decreased CD4 to CD8 ratio compared with controls ( p =0.02, Figs.…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, two studies have reported a decrease in the CD4 to CD8 lymphocyte ratio in the peripheral blood of TS patients [12,14]. Consistent with these two previous reports, we also found that TS patients have a decreased CD4 to CD8 ratio compared with controls ( p =0.02, Figs.…”
Section: Resultssupporting
confidence: 92%
“…This data is not entirely in concordance with some more recent studies [14,15]. Also Stenberg et al [16], that investigated immunoglobulin and lymphocyte subpopulations in TS to explain the increased incidence of otitis media of these individuals, did not find any major immunological deficiency.…”
Section: Immunity and Turner Syndromesupporting
confidence: 84%
“…These laboratory abnormalities seem to be clinically silent, since in TS infectious diseases are not more frequent than in general population, except for otitis media [11].…”
Section: Introductionmentioning
confidence: 99%